Narrative Branding Strategies on TikTok for Digital Culinary Heritage Sustainability: A Case Study of a Yogyakarta-Based MSME - Haniffah Nurul Eka Anisawati; Vani Dias Adiprabowo (INJECT (Interdisciplinary Journal of Communication), 2026)
Few studies have examined how strategic communication on TikTok can promote Indonesia's culinary heritage amid the dominance of global food trends. The entry of various foreign foods into Indonesia, driven by globalization, has shifted local gastronomy. This study examines the role of TikTok in promoting sustainable local gastronomy, using the @bakpiajuwarasatoe.id account as a case study. This account actively markets bakpia products as part of Yogyakarta's culinary heritage. The research method used is a descriptive qualitative case study approach. Data collection techniques include observing TikTok content, conducting semi-structured interviews with the account manager, and analyzing user interactions to understand the communication strategies in place. Data were analyzed thematically to identify patterns in visual storytelling, audience interaction, and brand collaboration. The study results show that the @bakpiajuwarasatoe.id account demonstrates how TikTok features can be strategically used through visuals, live broadcasts, and platform trends. The main conclusion offers strategic insight into how local culinary brands can leverage social media to strengthen cultural identity and market presence amid global competition. This study provides a theoretical contribution by offering new insights into the use of social media as a tool for sustainability diplomacy in promoting local cuisine. Practically, the findings can guide culinary MSMEs and academics in developing digital communication strategies to preserve sustainable gastronomy and raise awareness of local culinary potential and cultural heritage in shaping Indonesia's food future.